What school could be : insights and inspiration from teachers across America - Dintersmith, Ted (Princeton University Press, 2018)
Innovation expert Ted Dintersmith took a trip across America, visiting all fifty states in a single school year. He originally set out to raise awareness about the urgent need to reimagine education to prepare students for a world marked by innovation -- but America's teachers one-upped him. All across the country, he met teachers in ordinary settings doing extraordinary things, creating innovative classrooms where children learn deeply and joyously as they gain purpose, agency, essential skillsets and mindsets, and real knowledge. Together, these new ways of teaching and learning offer a vision of what school could be -- and a model for transforming schools throughout the United States. Better yet, teachers and parents don't have to wait for the revolution to come from above. They can readily implement small changes that can make a big difference. America's clock is ticking. Our archaic model of education trains our kids for a world that no longer exists, and accelerating advances in technology are eliminating millions of jobs. But the trailblazing of many American educators gives us reasons for hope. Capturing bold ideas from teachers and classrooms across America, Dintersmith provides a realistic and profoundly optimistic roadmap for creating cultures of innovation and real learning in all our schools.